Dietary diversity and associated factors among pregnant women attending antenatal care at public hospitals in North Shewa, Oromia, Ethiopia, 2023 - Alemu, Fikadu Tolesa; Desta, Adugna Alemu; Tola, Asfaw Getaye (Frontiers in Nutrition, 2024)
ABSTRACT Background: Adequate consumption of diversified food during pregnancy enables adequate intake of eleven important micronutrients. Pregnant women who consumed inadequate dietary diversity during pregnancy have high percentage of delivering preterm, still birth, low birth weight, and small for gestational age newborn. Objective: This study aims to assess dietary diversity and associated factors among pregnant women attending antenatal care at public hospitals of North Shewa, Oromia, Ethiopia, 2023. Methods and materials: An institution-based cross-sectional study was conducted on 400 pregnant women attending antenatal care. Study participants were selected by systematic random sampling method. Pre-tested structured interviewer administered questionnaire was used to collect dietary diversity. The questionnaire was adapted from a validated and modified individual dietary diversity guideline as recommended by Food and Agriculture Organization of the United Nations (FAO). Data were entered in to Epi data version 4.6 and exported to Statistical Package for the Social Sciences (SPSS) version 24 for analysis. Results from bivariate analysis of p<0.25 were moved to multivariable logistics regression model analysis. Any statistical test with the P-value <0.05 at 95% confidence interval was considered as statistically significant. Results: The study revealed that 55.4% of the pregnant women had adequate dietary diversity. Being urban dweller (adequate odds ratios (AOR=2.4. 95% CI: 1.1, 5.18)), being housewife (AOR=3.44, 95% CI: 1.37, 8.68), employed (AOR=3.69, 95% CI: 1.12, 12.16), merchant (AOR=3.43, 95% CI: 1.15, 10.24), daily laborer (AOR=3.66, 95% CI: (1.0, 13.45), low average monthly household income less than 500 Ethiopian birr (AOR=0.25, 95% CI: 0.07, 0.83), practicing home gardens (AOR=2.5, 95% CI : 1.39, 4.5), meal frequency three and above times per day (AOR=2.9, 95% CI: 1.64, 5.09), and receiving dietary counseling during antenatal care(AOR=3.56, 95% CI: 2.0, 6.35) were factors associated with pregnant women dietary diversity. Conclusions and Recommendations: This study found that 55.4% of pregnant women consumed adequate dietary diversity. Place of residence, women’s occupation, average monthly household income, practicing home gardens, meal frequency per day and receiving dietary counseling during antenatal care were strong predictors of adequate dietary diversity. Therefore, attention should be paid to pregnant women diet by health care provider during antenatal care.